AR Drum Circle: Real-Time Collaborative Drumming in AR - Hopkins, Torin; Weng, Suibi Che Chuan; Vanukuru, Rishi; Wenzel, Emma A.; Banic, Amy; Gross, Mark D.; Do, Ellen Yi-Luen (Frontiers in Virtual Reality, 2022)
AR Drum Circle, is an augmented reality (AR) platform we developed to facilitate a collaborative remote drumming experience. We explore the effects of virtual avatars that are rendered in a player’s view to provide the joy and sensation of co-present music creation. AR Drum Circle uses a head mounted AR display, providing players with visual effects to assist drummers in coordinating musical ideas while simultaneously using a latency-optimized remote collaboration service (JackTrip). AR Drum Circle helps overcome barriers in music collaboration introduced when using remote collaboration tools on their own, which typically do not support real-time video, lack spatial information, and volume control between players, all of which are important for in-person drum circles and music collaboration. This paper presents the results of several investigations: (1) analysis of an in-depth, free-form response survey of drumming communication provided by a small group of expert drummers, (2) observations and analysis of 20 videos of live drum circles, (3) a case study using the AR Drum Circle application in pairs of remotely located participants, and (4) a collaborative drumming case study using a popular networked conferencing application (Zoom). Findings suggest that substantial communicative information including facial expressions, hand-tracking, and eye-contact is lost when using AR alone. Findings also indicate that the AR Drum Circle application can make players less self-conscious and more willing to participate while playing drums improvisationally with others.